Daytime equatorial VHF radiowave scintillations and sporadic-E layer - Koparkar, P.V.; Rastogi, R.G.; Sastri, J.H. (My University, 1989)
Daytime VHF radiowave scintillations at Trivandrum are compared with the E-region irregularities at Kodaikanal. It is shown that daytime scintillations at Trivandrum are basically of two categories. One type of scintillations is associated with the q type of sporadic-E occurrence during normal electrojet condition and is weak with peak-to-peak fluctuations of 1-2 dB. The other type of scintillations is associated with blanketing type of sporadic-E occurrence during counter electrojet condition with magnitude greater than 5 dB.
Keywords: Ionospheric propagation; Magnetic equator; Equatorial electrojet; Counter electrojet; VHF radio wave